Physiological and Morphological Responses of Hydroponically Grown Pear Rootstock Under Phosphorus Treatment - Chen, Guodong; Li, Yang; Jin, Cong; Wang, Jizhong; Wang, Li; Wu, Juyou (Frontiers in Plant Science, 2021)
Phosphorus (P) is an essential macronutrient for the growth and development of fruit trees, playing an important role in photosynthesis, nucleic acid synthesis, and enzyme activity regulation. The plasticity of plant phenotypic has been investigated in diverse species under conditions of P-deficiency or P-excess. Based on these researches, P level fluctuations in different species result in different characteristics of the response. Nevertheless, little is known about the response of pear seedling rootstock (Pyrus betulifolia Bunge) to the changing of P levels. To explore the effects of different levels of P on the growth of pear seedling rootstock, we performed the hydroponic assays to determine and analyze the biological indexes including growth parameters, photosynthetic rate, root and shoot morphological traits, and concentrations of macro- and micronutrients. The results show that either deficiency or excess of P inhibited the growth and development of pear seedling rootstock. Root growth (down 44.8%), photosynthetic rate (down 59.8%), and acid phosphatase (ACP) activity (down 44.4%) were inhibited under the P-deficiency conditions (0 mM), compared with normal P conditions (1 mM). On the other hand, dark green leaves, suppression of root elongation (down 18.8%) and photosynthetic rate (down 25%) were observed under regimes of excessive P, compared with normal P conditions (1 mM). Furthermore, the root concentration of not only P, but also those of other mineral nutrients were affected by either P treatment. In brief, these results indicated that a careful choice of P fertilizer supply is crucial to ensuring normal growth and development of pear seedling rootstock.